2017
DOI: 10.33043/jsacp.9.2.95-111
|View full text |Cite
|
Sign up to set email alerts
|

“A Different Way”: The Experiences of Latinx Parents with School Counselors

Abstract: This phenomenological study aimed to identify the essence of the lived experiences of Latinx parents as they relate to school counselors. A Relational Cultural Theory (RCT) Framework was used to explore the experiences of Latinx parents with school counselors. Twelve Latinx parents were interviewed from three counties in a Southeastern state to share their experiences with school counselors to provide recommendations for practice to the school counseling specialty and school counselors in training. The five ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Tuttle and Johnson documented how language brokering can lead to negative outcomes, such as stress and parentification (e.g., taking on adult roles within the family), or positive outcomes, such as stronger family relationships and enhanced academic success. Consistent with the example described by Tuttle and Johnson, Tuttle and Haskins (2017) noted that school counselors can construct more culturally responsive interventions by addressing cultural barriers and acculturative stress to affirm a more welcoming environment for migrant families. In particular, Tuttle and Haskins described actions to increase the climate of safety and a more welcoming environment, such as forging relationships with families, developing community partnerships, integrating multiple languages into programming and curricular materials, and strengthening awareness of personnel for migrant family experiences.…”
Section: Review Of Relevant Literaturementioning
confidence: 60%
See 4 more Smart Citations
“…Tuttle and Johnson documented how language brokering can lead to negative outcomes, such as stress and parentification (e.g., taking on adult roles within the family), or positive outcomes, such as stronger family relationships and enhanced academic success. Consistent with the example described by Tuttle and Johnson, Tuttle and Haskins (2017) noted that school counselors can construct more culturally responsive interventions by addressing cultural barriers and acculturative stress to affirm a more welcoming environment for migrant families. In particular, Tuttle and Haskins described actions to increase the climate of safety and a more welcoming environment, such as forging relationships with families, developing community partnerships, integrating multiple languages into programming and curricular materials, and strengthening awareness of personnel for migrant family experiences.…”
Section: Review Of Relevant Literaturementioning
confidence: 60%
“…Furthermore, Rogers and colleagues (2015) found that racial and gender identity were highly correlated with each other and helped to shape Black boys’ social and school related adjustment over time. To illustrate the complexity of distinct yet interrelated identities, some authors found that when Latinx students attend schools where they are largely the majority, there is no link between ethnic identity and depressive symptoms, yet when Latinx students are highly represented within their schools and surrounding communities, ethnic identity is positively associated with positive health outcomes (Tuttle & Haskins, 2017).…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
See 3 more Smart Citations